The impact of value co-creation behavior on customers’ experiences with and loyalty to P2P accommodations - Lyu, Jing; Cao, Keyan; Yang, Shan (Frontiers in Psychology, 2022)
This study explores the impact of customers’ value co-creation behavior on their experiences with and loyalty to P2P accommodations. We propose a theoretical model integrating two lines of tourism research: customer value co-creation and customer experience. To extract the dimensions of customer experience and test the proposed model, 34 in-depth interviews were conducted along with a survey of Chinese Airbnb users. Structural equation modeling and mediation analysis were implemented to assess relationships involving customers’ value co-creation behavior, experience, and loyalty. Results indicate that customer citizenship behavior directly influences loyalty. In particular, relationships involving customers’ participation behavior and citizenship behavior with loyalty are both mediated by customer experience. Relevant implications and future research opportunities are discussed.